Medial Tibial Slope Determined by Plain Radiography Is Not Associated with Primary or Recurrent Anterior Cruciate Ligament Tears - Su, Alvin W.; Bogunovic, Ljiljana; Smith, Matthew V.; Gortz, Simon; Brophy, Robert H.; Wright, Rick W.; Matava, Matthew J. (The Journal of Knee Surgery, 2020)
Increased tibial slope may be associated with anterior cruciate ligament (ACL) injuries, although potential confounding effects from various patient characteristics and radiographic quantification methods have not been rigorously studied. The association of the slope of the lateral plateau with recurrent ACL injury after primary ACL reconstruction has recently been reported, but the role of medial slope is less well defined. The purpose of this study was to (1) assess medial tibial slope measurement reliability among examiners, (2) compare medial tibial slope values between patients undergoing primary ACL reconstruction, reinjured patients undergoing revision ACL reconstruction, and a control cohort with an intact ACL, (3) analyze if the medial tibial slope is an independent risk factor for noncontact ACL injury, and (4) assess how different anatomical references affect medial tibial slope values. A total of 206 patients were enrolled into one of three groups: (1) ACL-intact controls (CONTROL, n = 83), (2) first-time ACL-injured patients (PRIMARY, n = 77), and (3) patients undergoing revision ACL reconstruction (REVISION, n = 46). Three fellowship-trained sports medicine surgeons performed repeated measurements of plain lateral radiographs. The medial tibial slope was determined by three anatomical references: anterior tibial cortex (anterior tibial slope [ATS]), posterior tibial cortex (posterior tibial slope [PTS]), and the anatomical long axis of the tibia (composite tibial slope [CTS]). Substantial intra- and interobserver reliabilities were established by the intraclass correlation coefficient of 0.73 to 0.89. There was no difference in CTS, ATS, or PTS comparing the CONTROL, PRIMARY, and REVISION groups upon univariate analyses. Multivariable logistic regression model showed that none of the slope values was independently associated with ACL injury. The mean ATS for all 206 subjects was 4 and 8 degrees greater than the mean CTS and PTS, respectively. ATS correlated only moderately to PTS. We concluded that medial tibial slope measured on radiographs is not associated with primary or recurrent ACL injury, and has substantial variation and suboptimal correlation when using different anatomical references despite good inter- and intraobserver reliabilities.
Keywords: anterior cruciate ligament; ACL injury; revision ACL; knee biomechanics; tibial slope